2017
DOI: 10.1186/s12957-017-1285-2
|View full text |Cite
|
Sign up to set email alerts
|

Giant gastrointestinal stromal tumor with predominantly cystic changes: a case report and literature review

Abstract: BackgroundGastrointestinal stromal tumors (GISTs) rarely present with predominantly cystic changes. Here, we report a case of giant GIST of the stomach with predominantly cystic changes in a 74-year-old female patient.Case presentationThe tumor was 10 cm × 15 cm in size and positive for CD117, H-caldesmon, and DOG-1. Complete surgical resection was performed without regional lymphadenectomy. The patient recovered uneventfully and no recurrence occurred.ConclusionsThe case illustrates that GIST with cystic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…GISTs typically form a regular, soft, solid mass, but they may also rarely present as cyst‐predominant lesions. GISTs with large cystic changes tend to grow exophytically from the gastrointestinal tract wall, and in some cases can be over 10 cm in diameter . It appears that cystic changes are more frequently observed in high‐grade GISTs, possibly due to the poor blood supply to the aggressively growing tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GISTs typically form a regular, soft, solid mass, but they may also rarely present as cyst‐predominant lesions. GISTs with large cystic changes tend to grow exophytically from the gastrointestinal tract wall, and in some cases can be over 10 cm in diameter . It appears that cystic changes are more frequently observed in high‐grade GISTs, possibly due to the poor blood supply to the aggressively growing tumor.…”
Section: Discussionmentioning
confidence: 99%
“…GISTs with large cystic changes tend to grow exophytically from the gastrointestinal tract wall, and in some cases can be over 10 cm in diameter. [14][15][16] It appears that cystic changes are more frequently observed in high-grade GISTs, possibly due to the poor blood supply to the aggressively growing tumor. It was also reported that liquefactive necrosis, scattered empty spaces with lymphoid infiltration and loose hyaline material, can be observed in nearly half of GIST tumors, but without prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Although GIST is the most common mesenchymal tumor of the gastrointestinal tract, its diagnosis can be challenging [1]. Most atypical presentations are diagnosed only on histopathological basis after surgical resection [5]. The atypical presentation of GIST in our patient, with complete cystic degeneration, is no exception for the same although the diagnosis was made intraoperatively.…”
Section: Discussionmentioning
confidence: 67%
“…Small cystic areas are frequently observed in GISTs with large size, but GISTs rarely manifest predominantly as cystic tumors. Cases of this uncommon form have been described but no retrospective study has been reported in the English literature (Hamza et al 2016 ; Okano et al 2015 ; Shaikh et al 2015 ; Sun et al 2016 ; Takahashi et al 2010 ; Wang et al 2017 ; Zhu et al 2014 ). In addition, clinical follow-up information was not available in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…GISTs are typically solid, sometimes with small cystic area developed, but rarely manifest as predominant cystic neoplasms. To date, reports of this uncommon form of GISTs have comprised mostly case reports focusing mainly on its clinical and radiographic features (Hamza et al 2016 ; Okano et al 2015 ; Shaikh et al 2015 ; Sun et al 2016 ; Takahashi et al 2010 ; Wang et al 2017 ; Zhu et al 2014 ). There is very limited information in the literature relating to the pathologic features and prognoses of GISTs undergoing extensive cystic change.…”
Section: Introductionmentioning
confidence: 99%